2006
DOI: 10.1002/jso.20580
|View full text |Cite
|
Sign up to set email alerts
|

High operative risk of cool‐tip radiofrequency ablation for unresectable pancreatic head cancer

Abstract: Standard use of cool-tip RFA was dangerous for pancreatic head cancer close to portal vein, in which a 5-mm minimum safe distance between RFA site and major peripancreatic vessels might not be enough to avoid injury to the vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
91
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 20 publications
5
91
2
1
Order By: Relevance
“…Quite all pancreatic studies have focused on the feasibility and complications of intraoperative RFA. 19,21,35,49 The present study demonstrated the efficacy of the percutaneous ablation procedure with no complications reported in the 18 patients. Technical success, in fact, was obtained in every treated patient with a complete necrosis of an ablated area that covered more than 50% of the lesion extension in 93% of the cases and with no immediate but also delayed complications.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Quite all pancreatic studies have focused on the feasibility and complications of intraoperative RFA. 19,21,35,49 The present study demonstrated the efficacy of the percutaneous ablation procedure with no complications reported in the 18 patients. Technical success, in fact, was obtained in every treated patient with a complete necrosis of an ablated area that covered more than 50% of the lesion extension in 93% of the cases and with no immediate but also delayed complications.…”
Section: Discussionsupporting
confidence: 62%
“…During treatment, the tip of the needle must be kept at almost 5 mm from the sensitive structures such as the duodenum and peripancreatic vessels. [35][36][37] Regarding temperature, since protein denaturation begins at 50 C to 60 C, the higher temperatures used during the procedure achieve homogeneous necrosis. On the other hand, the use of too high temperatures (105 C) is proved to increase the risk of complications without a favorable effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, similar devices with similar principles have been employed for either aim in the liver and more recently in the pancreas. For example, similar or identical RF cool-tip electrodes have been employed for either radiofrequency ablation or radiofrequency-assisted transection of the liver 7,26 and the pancreas 14,24,27,28 . However, RF pancreatic ablation has been repeatedly warned to be associated with severe necrotizing pancreatitis with lifethreatening haemorrhagic complications, among other critical and dangerous complications 15,27 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, similar or identical RF cool-tip electrodes have been employed for either radiofrequency ablation or radiofrequency-assisted transection of the liver 7,26 and the pancreas 14,24,27,28 . However, RF pancreatic ablation has been repeatedly warned to be associated with severe necrotizing pancreatitis with lifethreatening haemorrhagic complications, among other critical and dangerous complications 15,27 . Even though, recent experiences seem to have reduced these severe complications using some prophylactic measures to avoid severe acute pancreatitis (such as exocrine secretion inhibition or reducing the ablative area to the tumor) 24,28,29 or thermal damage of the duodenum (using a duodenal cooling) 30 , this technique should be considered with extreme caution because of these serious complications 8 .…”
Section: Discussionmentioning
confidence: 99%